Prerequisites for stretching use in physical education of high school female students - Natalia Bielikova; Nina Dedeliuk (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2020)
The article deals with flexibility as one of the leading physical characteristic of a person, presents the scientific view of the types of flexibility and their description, as well as peculiarities of flexibility development at different stages of human life. The paper also covers flexibility development methods using various exercises, including different types of stretching. The author considers the possibilities of stretching use in physical education of secondary schools students in Ukraine.